Xpert® MTB/RIF Ultra Accuracy in Pulmonary TB Diagnosis: Comparative Analysis with Mycobacterial Growth Indicator Tube 960 System - Arifatun Nasicha; Ni Made Mertaniasih; Eko Budi Koendhori; Pepy Dwi Endraswari; Ariani Permatasari; Atika (Journal of Pure and Applied Microbiology)
Tuberculosis (TB) is an infectious illness induced by Mycobacterium tuberculosis (MTB), a principal cause of mortality globally. The incidence of TB in Indonesia is increasing every year. WHO recommends Xpert MTB/RIF Ultra, which is sensitive and specific, as an initial method of TB diagnosis that detects IS1081/IS6110 of the Mycobacterium tuberculosis complex (MTBC). The study intends to analyze the accuracy of Xpert Ultra with Mycobacterial Growth Indicator Tube (MGIT) 960 culture system of pulmonary TB in the Clinical Microbiology Laboratory of Dr. Soetomo Academic Hospital, Indonesia. This was an analytical, observational, and cross-sectional study that included 39 of 382 sputum samples that met the inclusion and exclusion criteria from suspected pulmonary TB patients. The result showed that 56.4% (22/39) were adults, and 41% were elderly (>60 years), 61.5% (24/39) were male, and 43% of them were smokers. Demographic factors, epidemiology, patients’ clinical conditions, and chest x-ray patterns all have no significant value on suspected pulmonary TB cases (p > 0.05). Xpert Ultra sensitivity was 83.3%, specificity 82.5% and accuracy 84.6%. There are no statistical differences between the two diagnostic methods (p = 0.687, McNemar’s). In conclusion, Xpert Ultra can diagnose pulmonary TB as well as MGIT 960 system culture. Although demographic factor, epidemiology, clinical symptoms, and also chest x-ray pattern cannot confirm the diagnosis of pulmonary TB, it is necessary to carry out confirmation tests under the guidelines.